DESIGNING OF ELECTRONIC LEARNING TOOLS IN THE CONTEXT OF MODERNIZATION OF CONTINUOUS VOCATIONAL EDUCATION - Kseniya R. Ovchinnikova (Высшее образование в России)
The article substantiates the need of designing electronic learning tools in the context of modernization of continuing professional education. These tools should provide specific structure, content and focus of learning and cognitive activities of students. The article proposes tool support for didactic designing of electronic means of instruction.